Variation in incubation effort during egg laying in the Mountain Bluebirds and its association with hatching asynchrony. Issue 3 (23rd August 2013) - Johnson, L. Scott; Napolillo, Felicia M.; Kozlovsky, Dovid Y.; Hebert, Rachel M.; Allen, Allison
ABSTRACT: Females in many bird species reportedly begin incubation prior to clutch completion, but the nature of such incubation and the degree to which it varies among females remains undescribed for almost all species. We used continuous recording of nest‐cup temperatures to document incubation effort during egg laying at 57 Mountain Bluebird ( Sialia currucoides ) nests in a high‐elevation Wyoming population. We then asked whether such effort predicted the degree to which eggs hatch asynchronously. Although substantial egg heating could begin abruptly late in laying (previously reported as the norm for this species) or even after clutch completion, we found that most (>90%) females began incubation gradually, engaging in a few (usually 1–8), brief (<10 min) bouts of heating on the day they laid their first or second egg. Thereafter, females varied markedly in when they increased incubation effort and by how much. The onset of nocturnal incubation also varied, with females beginning to incubate at night after laying their prepenultimate, penultimate, or last egg and not always initially incubating through the night. As an index of the total amount of heat applied to eggs during laying, we calculated the cumulative number of degrees by which nest‐cup temperatures exceeded the threshold temperature required for embryonic development. This value varied by more than 150‐fold between nests and explained >50% of the variation in hatching asynchrony. Our results thus provide strong support for the widely held, but rarely tested, assumption that parent birds can have substantial control over the degree of hatching asynchrony by varying the amount of incubation done prior to clutch completion.